2017
DOI: 10.18632/oncotarget.16278
|View full text |Cite
|
Sign up to set email alerts
|

Renal sympathetic denervation guided by renal nerve stimulation to treat ventricular arrhythmia in CKD patients with ICD

Abstract: Chronic kidney disease (CKD) patients on stage 4 present greater risk rates for malignant ventricular arrhythmia events. This study examined patients with CKD in stages 1, 2, 3 and 4, left ventricular dysfunction and automatic implantable cardioverter-defibrillator (ICD). Our goal was to record the appropriate therapies, “Anti-tachycardia Therapy Pacing” (ATP) and shock events during the 18 months of follow-up and compare the incidence and severity of these at different stages of CKD, mainly in patients with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…After RDN, a more blunted BP rise response with RNS was associated with greater reduction of ambulatory BP from 3 to 6 months. 81 Interestingly, studies using RNS to predict response to RDN in treatment of atrial fibrillation 82 and ventricular tachycardia 83 showed similar findings. These proof-of-concept studies involving RNS were often conducted with the use of conventional catheters designed for electrophysiology studies, followed by RDN using currently available RDN catheters.…”
Section: How Can the Rdn Procedures Be Optimized Further?mentioning
confidence: 82%
“…After RDN, a more blunted BP rise response with RNS was associated with greater reduction of ambulatory BP from 3 to 6 months. 81 Interestingly, studies using RNS to predict response to RDN in treatment of atrial fibrillation 82 and ventricular tachycardia 83 showed similar findings. These proof-of-concept studies involving RNS were often conducted with the use of conventional catheters designed for electrophysiology studies, followed by RDN using currently available RDN catheters.…”
Section: How Can the Rdn Procedures Be Optimized Further?mentioning
confidence: 82%
“…In a cohort of HF subjects, NT-proBNP levels were reduced by RDN, which was well tolerated and did not worsen the function of the heart and the kidneys (Hopper et al, 2017). Also, the proportion of refractory VAs and ICD shocks plunged post-RDN in another cohort with late stages of HF and CKD (Kiuchi et al, 2017).…”
Section: Renal Denervationmentioning
confidence: 94%
“…In HF subjects, RDN fell NT-pro BNP concentrations and was harmless, showing no worsening of other indices of cardiac and renal function [119]. Another study reported a reduction in the rate of malignant VAs and proper ICD therapies in advanced stages of chronic kidney disease (CKD) and HF patients [120].…”
Section: Treatment Approaches Targeting the Sns: Renal Denervationmentioning
confidence: 99%
“…SNS management has emerged as a useful tool for diagnosing, preventing and treating HF, VAs, and SCD [59,120,121]. However, its configuration and clinical manifestations and disturbances are numerous and multifaceted.…”
Section: Sns Management To Diagnose Prevent and Treat Hf Vas Anmentioning
confidence: 99%
See 1 more Smart Citation